An Analysis of Students' Learning Styles in English Teaching and Learning Process - Lahita, Nanda (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The objective of the study is to identify the students’ learning styles including visual, auditory or kinaesthetic in English teaching and learning process. This research is descriptive qualitative research. This research was conducted at Institute of Sunan Drajat Islamic Boarding School which the participants of this research were the first semester students of islamic counseling and guidance department program in the academic year of 2023 / 2024. The number of the subjects were 35. The data collection was done by giving a questionnaire. The questionnaire was adapted from the VAK learning styles test created by Chislett and Chapman (2005) which consists of 30 questions determining students’ learning style. The research findings indicated that there are 16 (45,71%) students categorized as visual learners, 12 (34,28%) students categorized as auditory learners, and 7 (20%) students categorized as kinaesthetic learners. Visual learners prefer to learn by seeing and watching demonstration. Auditory learners prefer to learn by hearing. And the kinaesthetic learners prefer learn by doing